Distinct processes mediate glycoprotein and glycopeptide export from the endoplasmic reticulum in Saccharomyces cerevisiae. - Römisch, K (1992)
Protein and peptide export from the Saccharomyces cerevisiae endoplasmic reticulum was examined in vitro using the secretory protein pro-alpha-factor and a synthetic tripeptide containing the acceptor site for N-linked glycosylation as substrates. The release of both glycosylated pro-alpha-factor and glycotripeptide from the endoplasmic reticulum was dependent on cytosol, temperature, and ATP. Antibodies against two proteins essential for the formation of transport vesicles, Sec23p and p105, inhibited glyco-pro-alpha-factor exit from the endoplasmic reticulum but did not affect the release of the glycosylated tripeptide. Furthermore, in contrast to pro-alpha-factor, the exported glycopeptide was not associated with a membrane fraction and did not acquire Golgi-specific alpha(1-6)-linked mannose residues. We conclude that the glycosylated tripeptide leaves the yeast endoplasmic reticulum by a route different from the secretory pathway, possibly through an ATP-driven pump.